PENERAPAN METODE TILAWATI PADA MATA PELAJARAN BACA TULIS AL-QUR’AN DI SDIT MUKHLISIIN KABUPTEN GOWA - ., Hartono (Inspiratif Pendidikan, 2018)
This study discusses the Application of the Tilawati Method to the Qur'anic Reading Subjects at SDIT Mukhlisiin. The aim is to find out the form of implementation of the Tilawati Method in the Koran reading and writing subjects in SDIT Mukhlisiin, the supporting factors and obstacles to the implementation of the tilawati method in the Koran reading and writing in SDIT Mukhlisiin as well as solutions to the inhibiting factors in implementation the application of the tilawati method to the Qur'anic literacy subjects at SDIT Mukhlisiin. This type of research is classified as qualitative with a research approach that is a scientific approach and a scientific study approach. The scientific approach includes the sociological approach and the scientific study approach which includes interdisciplinary, namely pedagogical approaches and psychological approaches. The results of this study indicate that the Implementation of the Tilawati Method in the Qur'anic literacy subjects at SDIT Mukhlisiin runs well, but some of the Qur'anic literate teachers have not been maximal in applying the tilawah method to the reading and writing subjects 's at SDIT Mukhlisiin because the time given is still minimal. The application of the tilawati method to the Koran reading and writing in SDIT Mukhlisiin is expected to contribute to the teachers who come in direct contact with the students, especially the Koran literate teachers in order to maximize their duties as professional educators , and develop themselves in applying the recitations method.